Prontidão para a prática regular de atividade física em adultos do sul do Brasil. - Dumith, Samuel de Carvalho (2006)
Background: Evidences suggest that physical activity (PA) interventions tailored to individual s stages of change (SoC) are more effective in promote behavior change than one-size-fits-all interventions. However, only a few researches have investigated these stages towards PA behavior in representative samples of the population. Thus, the purpose of this study was to determine the prevalence and factors associated with the SoC for PA in a probabilistic sample of adults aged 20 years or over. Methods: A population-based survey was undertaken in Pelotas, Southern Brazil, in 2005. The SoC for PA (precontemplation, contemplation, preparation, action and maintenance) were evaluated, and PA was defined as being engaged in moderate-tovigorous PA for at least 20 minutes on three times per week. The covariates collected in the questionnaire were: sex, age, skin color, marital status, education level, economic status, family income, smoking, body mass index (BMI) and self-reported health status. Data analyses were performed through Poisson regression taking the sampling design into account. Results: Face-to-face interviews were applied to 3136 individuals, corresponding to a response rate of 93.5%. Almost 70% of the respondents were not engaged in PA, and more than one third did not intend to do so within the next six months. Non-white, elderly, smokers and individuals who lived with a partner were more likely to be in the precontemplation stage. This likelihood decreased with socioeconomic status, BMI and self-reported health status. Conclusions: Despite the large proportion of inactive individuals, most do not intend to engage in PA. These findings are of relevance to improve health behaviors and to plan health promotion strategies aimed at increasing the level of PA in the population.